Biomass Charcoal Properties Changes During Storage. (May 2017) - Wang, L.; Barta-Rajnai, E.; Hu, K.; Higashi, C.; Skreiberg, Ø.; Grønli, M.; Czégény, Z.; Jakab, E.; Myrvågnes, V.; Várhegyi, G.; Antal, M.J.
Abstract: In this work, effects of storage time and conditions on the properties of one woody charcoal were studied. Prior to the storage test, the untreated charcoal was characterized by thermogravimetry/mass spectrometry (TG/MS). Weight loss (TG) and evolution profile curves of selected gaseous products were obtained from charcoal pieces that have various appearances, apparent densities and sizes. The result implies that the charcoal pieces have experienced different carbonization conditions. The charcoal samples were collected during the storage test under well controlled conditions and further characterized. It was found that the volatile content of the collected charcoal samples decreases along the storage time. The ash content of sampled charcoal only changed slightly. Accordingly, the fixed carbon content of sampled charcoal decreased about 3% in comparison to the initially loaded untreated charcoal samples. Such decrease of fixed carbon content of charcoal during storage might cause considerable reduction of profitability for an industry that consumes large amounts of charcoal at a relatively high price.